ENSURING FOOD SAFETY OF PRODUCTS PLANT ORIGIN IN THE EUROPEAN AND CUSTOMS UNIONS - T. V. Shchedrina; V. N. Orobinskaya; D. S. Sedykh (Современная наука и инновации)
Food safety in modern conditions has an increasing impact on the health indicators of various population groups, on the growth and development of children, schoolchildren, and various spheres of human activity. One of the ways to improve the organization of safe food is to use the experience of the European Union.